2001
DOI: 10.11150/kansenshogakuzasshi1970.75.775
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Anti-Cytomegalovirus IgG Antibody Positive Rate and Cytomegalovirus Mononucleosis in Adults

Abstract: We analyzed anti-Cytomegalovirus (CMV) IgG and IgM antibody (EIA) and anti-Epstein-Barr virus (EBV) viral capsid antigen (VCA) IgG and IgM antibody (FA) in adults during 1994-1999. We examined these IgM sero-positive patient's medical records, and diagnosed CMV mononucleosis and EBV mononucleosis. Anti-CMV antibody positive rates decreased from 87.6% in 1994 to 77.8% in 1999. Especially in twenties, anti-CMV antibody positive rates decreased from 65.2% in 1994 to 53.3% in 1999. On the other hand, anti-EBV VCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Second, our preoperative examination did not include serologic CMV antibody status of either the recipients or donors; therefore we had no information on high-risk recipients with recipient-negative and donor-positive CMV serostatus. With regard to this point, however, CMV is endemic in Japan (81.7% of adults were CMV IgG positive (18), which suggests that almost all of the recipients in the present study were likely CMV IgGpositive (19). Third, this study was a not a multi-center, double-blinded study.…”
Section: Discussionmentioning
confidence: 98%
“…Second, our preoperative examination did not include serologic CMV antibody status of either the recipients or donors; therefore we had no information on high-risk recipients with recipient-negative and donor-positive CMV serostatus. With regard to this point, however, CMV is endemic in Japan (81.7% of adults were CMV IgG positive (18), which suggests that almost all of the recipients in the present study were likely CMV IgGpositive (19). Third, this study was a not a multi-center, double-blinded study.…”
Section: Discussionmentioning
confidence: 98%
“…The positive detection rate of anti-CMV antibody in Japanese people, most of whom were infected with the virus during infancy was high being 80 to 90% [14], and higher than that among people in the United States [15]. In recent years, however, positive detection rate of the antibody among young Japanese people has decreased to around 60%, possibly because of decreased horizontal infection in infancy [14].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, positive detection rate of the antibody among young Japanese people has decreased to around 60%, possibly because of decreased horizontal infection in infancy [14]. Therefore, the incidence of CMV-IM, which was low when compared with that of EBV-IM, is assumed to have increased in recent years [14].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a recent decrease in the prevalence of the anti-CMV antibody, particularly in young adults (18,19). Consequently, the number of cases of acute CMV infection in immunocompetent adults appears to be increasing, along with an increase in the incidence of severe complications.…”
Section: Discussionmentioning
confidence: 99%